REPRESENTASI SIMBOLIK: MAKNA RADIKALISME DALAM MEDIA SOSIAL INSTAGRAM - Fernando, Henky (Universitas Negeri Malang, 2021)
The Instagram social media platform is not only used as a forum for friendship, it turns out to be an arena that is so free for the public to carry out various expressions, as has been done by Instagram social media users in depicting and interpreting radicalism symbolically. The symbols chosen by Instagram social media users to represent radicalism in Indonesia certainly have very strong reasons. Therefore, this paper aims to describe the symbols of radicalism as well as to explain how Instagram social media users interpret radicalism. This paper uses a virtual ethnographic approach that is descriptive, qualitative, and uses observational methods in the data collection process. The findings in this paper indicate the use of state symbols, organizational attributes, and ideological symbols in representing radicalism in Indonesia. The use of these symbols refers to the three meanings of Instagram social media users, namely, the impact caused by the practice of dehumanizing radicalism, the emergence of radicalism is inseparable from the demoralization that occurs in society, radicalism has also caused anxiety and fear amidst the fear of crime. Based on the findings of this paper, this paper sees the importance of a comprehensive understanding of the symbolic representation of radicalism memes in the ideas of social media users on Instagram as a new effort to find solutions to the rampant practice of radicalism that uses social media to spread its movement in Indonesia. Platfrom media sosial Instagram tidak hanya dimanfaatkan sebagai wadah pertemanan semata, ternyata juga menjadi arena yang begitu bebas untuk khalayak dalam melakukan berbagai ekspresi, sebagaimana yang dilakukan oleh pengguna media sosial Instagram dalam menggambarkan dan memaknai radikalisme secara simbolik. Simbol-simbol yang dipilih oleh pengguna media sosial Instagram dalam mewakili radikalisme di Indonesia tentunya memiliki alasan yang sangat kuat. Oleh karena itu, tulisan ini selain bertujuan untuk mendeskripsikan simbol-simbol dari radikalisme, juga untuk menjelaskan bagaimana pengguna media sosial Instagram dalam memaknai radikalisme. Tulisan ini menggunakan pendekatan etnografi virtual bersifat deskriptif, kualitatif, dan menggunakan metode observasi dalam proses pengumpulan data. Adapun temuan dalam tulisan ini menunjukan adanya penggunnaan simbol-simbol negara, atribut organisasi, dan simbol-simbol ideologis dalam mewakili radikalisme di Indonesia. Penggunaan simbol-simbol tersebut merujuk pada tiga pemaknaan pengguna media sosial Instagram yaitu, dampak yang ditimbulkan oleh praktik radikalisme dehumanisasi, munculnya radikalisme tidak terlepas dari demoralisasi yang terjadi di masyarakat, radikalisme telah pula menyebabkan keresahan dan ketakutan ditengah-tengah masyarakat fear of crime. Berdasarkan hasil temuan dari tulisan ini, maka tulisan ini melihat pentingnya pemahaman yang komprehensif mengenai representasi simbolik meme radikalisme dalam gagasan pengguna media sosial Instagram sebagai upaya baru dalam menemukan solusi atas maraknya praktik radikalisme yang menfaatkan media sosial untuk menyebarluaskan gerakannya di Indonesia.